Association of anxiety and depression with hypertension control: a US multidisciplinary group practice observational study. Issue 11 (November 2015) - Ho, Aaron K.; Thorpe, Carolyn T.; Pandhi, Nancy; Palta, Mari; Smith, Maureen A.; Johnson, Heather M.
Abstract : Objective: The presence of a mental health disorder with hypertension is associated with higher cardiovascular disease mortality than hypertension alone. Although earlier detection of hypertension has been demonstrated in patients with anxiety and depression, the relationship of mental health disorders to hypertension control is unknown. Our objective was to evaluate rates and predictors of incident hypertension control among patients with anxiety and/or depression compared with patients without either mental health diagnosis. Methods: A 4-year retrospective analysis included 4362 patients, at least 18 years old, who received primary care in a large academic group practice from 2008 to 2011. Patients met The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure criteria and had a hypertension diagnosis. Kaplan–Meier analysis estimated the probability of achieving control for patients with and without anxiety and/or depression. Cox proportional hazard models were fit to identify predictors of time to control. Results: Overall, 13% ( n = 573) had a baseline diagnosis of anxiety and/or depression. Those with anxiety and/or depression demonstrated more primary care and specialty visits than those without either condition. After adjustment, patients with anxiety and/or depression had faster rates of hypertension control (hazard ratio [HR] 1.22; 1.07–1.39] than patients without either diagnosis. Other associations of faster hypertension control included female gender (HR 1.32; 1.20–1.44), absence of tobacco use (HR 1.17; 1.03–1.33), Medicaid use (HR 1.27; 1.09–1.49), and a higher Adjusted Clinical Group Risk Score (HR 1.13; 1.10–1.17), a measure of healthcare utilization. Conclusion: Greater healthcare utilization among patients with anxiety and/or depression may contribute to faster hypertension control.